Biogeographic Differences in the Microbiome and Pathobiome of the Coral Cladocora caespitosa in the Western Mediterranean Sea - Rubio-Portillo, Esther; Kersting, Diego K.; Linares, Cristina; Ramos-Esplá, Alfonso A.; Antón, Josefa (Frontiers in Microbiology, 2018)
The endemic Mediterranean zooxanthellate scleractinian reef-builder Cladocora caespitosa is among the organisms most affected by warming-related mass mortality events in the Mediterranean Sea. Corals are known to contain a diverse microbiota that plays a key role in their physiology and health. Here we report the first study that examines the microbiome and pathobiome associated with C. caespitosa in three different Mediterranean locations (i.e. Genova, Columbretes Islands and Tabarca Island). The microbial communities associated with this species showed biogeographical differences, but shared a common core microbiome that probably plays a key role in the coral holobiont. The putatively pathogenic microbial assemblage (i.e. pathobiome) of C. caespitosa also seemed to depend on geographic location and the human footprint. In locations near the coast and with higher human influence, the pathobiome was entirely constituted by Vibrio species, including the well-known coral pathogens V. coralliilyticius and V. mediterranei. However, in the Columbretes Islands, located off the coast and the most pristine of the analyzed locations, no changes among microbial communities associated to healthy and necrosed samples were detected. Hence, our results provide new insights into the microbiome of the temperate corals and its role in coral health status, highlighting its dependence on the local environmental conditions and the human footprint.